Component modelling of 3D laser cut joints with CHS columns and through-all members. (January 2023) - Latour, M.; Di Benedetto, S.; Saldutti, A.; Rizzano, G.; Kanyilmaz, A.; Castiglioni, C.A.
Abstract: 3D laser cutting technology is a new automatised industrial process allowing the development of a range of novel applications in civil engineering. Its main advantage derives from the possibility to manufacture easily tridimensional cutting shapes with high precision (accuracy of about 10 μ m ), minimising the hole size, optimising the welding quantity and costs. This technology is up to thirty times faster than traditional methods since all the operations are programmed and fully realised by the machine, avoiding any intervention of operators, eliminating human errors and increasing the quality level. 3D-LCT allows joining hollow section profiles to through-all members with a straightforward production process. The main feature of joints with passing-through profiles is the higher flexural strength and stiffness compared to traditional connections without additional costs. Nevertheless, considering the recent development of these joints, currently, there are no codified rules, and their design usually implies the use of FEM. This work aims to take a step towards developing simple analytical tools for designing and modelling such connections through the component method, currently codified in EC3 part 1.8. Within this framework, the subject of the paper is the study of the behaviour of one of the main elementary components characterising the response of beam-to-column joints with CHS columns and I-beams, which is the " passing-through plate transversally welded to the column in tension/compression ". This component idealises the behaviour of the passing-through beam flange plates (in tension/compression) at the attachment with a CHS column. Its response is significant for the overall joint behaviour because it governs the deformability of the connection and may limit the joint's resistance due to the CHS tube's local failure. This paper presents the results of three monotonic tests of sub-assemblies of this joint component, showing the typical failure mode and the component behaviour. Subsequently, a FE model is built with ABAQUS software, carrying out parametric studies to individuate the main parameters influencing the behaviour of these joints. Finally, equations to predict the stiffness and strength are provided, showing the accuracy obtained. Highlights: Experimental tests on CHS to through-all plate joints are presented and discussed. A FE model of the connection is built, validated against experimental results and exploited to perform a parametric study. Equations to predict the strength and stiffness of CHS to through-all plate connections have been defined. The accuracy of the equation is verified against FE data showing high accuracy.